The Relationship between Peer Social Support and Emotional Intelligence on Subjective Well-Being of Students in Class XI SMAN 31 Jakarta - Pranida, Risa Putri; Tazkiyah, Nuril (Formosa Journal of Multidisciplinary Research, 2024)
This research aims to determine the relationship between peer social support and emotional intelligence on the subjective well-being of class XI students at SMAN 31 Jakarta. The population in this study was 214 students and 136 students were sampled in this study. The sampling technique for this study used proportionate stratified random sampling. The measuring instruments used were the subjective well-being scale (26 items α = 0.840), the peer social support scale (23 items α = 0.665) and the emotional intelligence scale (33 items α = 0.948). The results of the research show that there is a positive relationship between social support from peers and subjective well-being of 0.365 and there is a positive relationship between emotional intelligence and subjective well-being of 0.385. Furthermore, the results of data analysis with multivariate correlation using SPSS 22.0 for Windows obtained a correlation coefficient of R = 0.513 and significance level (p) = 0.000 < 0.05. This shows that there is a relationship between peer social support and emotional intelligence on the subjective well-being of class XI students at SMAN 31 Jakarta.